The use of non-standard motorcycle helmets in low- and middle-income countries: a multicentre study. Issue 3 (9th November 2012) - ,; Ackaah, Williams; Afukaar, Francis; Agyemang, Williams; Thuy Anh, Trinh; Hejar, A R; Abdul, Ghaffar; Gururaj, Gopalkrishna; Elisa, Hidalgo-Solórzano; Martha, Híjar; Hyder, Adnan A; Inclán-Valadez, Cristina; et al.
Abstract : Background: The use of non-standard motorcycle helmets has the potential to undermine multinational efforts aimed at reducing the burden of road traffic injuries associated with motorcycle crashes. However, little is known about the prevalence or factors associated with their use. Methods: Collaborating institutions in nine low- and middle-income countries undertook cross-sectional surveys, markets surveys, and reviewed legislation and enforcement practices around non-standard helmets. Findings: 5563 helmet-wearing motorcyclists were observed; 54% of the helmets did not appear to have a marker/sticker indicating that the helmet met required standards and interviewers judged that 49% of the helmets were likely to be non-standard helmets. 5088 (91%) of the motorcyclists agreed to be interviewed; those who had spent less than US$10 on their helmet were found to be at the greatest risk of wearing a non-standard helmet. Data were collected across 126 different retail outlets; across all countries, regardless of outlet type, standard helmets were generally 2–3 times more expensive than non-standard helmets. While seven of the nine countries had legislation prohibiting the use of non-standard helmets, only four had legislation prohibiting their manufacture or sale and only three had legislation prohibiting their import. Enforcement of any legislation appeared to be minimal. Interpretation: Our findings suggest that the widespread use of non-standard helmets in low- and middle-income countries may limit the potential gains of helmet use programmes. Strategies aimed at reducing the costs of standard helmets, combined with both legislation and enforcement, will be required to maximise the effects of existing campaigns.